2023
DOI: 10.1186/s12903-023-02787-5
|View full text |Cite
|
Sign up to set email alerts
|

Salivary macrophage chemokines as potential biomarkers of gingivitis

Abstract: Objective The present study aimed to analyze the salivary levels of macrophage-activating factor (MAF), macrophage-chemotactic factor (MCF), and macrophage migration inhibitory factor (MIF) in healthy and gingivitis patients, and to correlate between the concentrations of these chemo attractants with the intensity of gingival inflammation clinically. Methods Sixty saliva specimens were collected from periodontally healthy (n = 30), and gingivitis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…There was no difference between periodontal health and diseases at salivary-MIF levels in this study. These results are contrary to other studies showing increased saliva-MIF levels in gingivitis [ 39 ] and periodontitis [ 38 , 39 ] when compared with periodontally healthy controls. However, in agreement with our results, in a previous study difference was not shown at MIF levels in saliva between periodontally healthy, gingivitis and periodontitis patients [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…There was no difference between periodontal health and diseases at salivary-MIF levels in this study. These results are contrary to other studies showing increased saliva-MIF levels in gingivitis [ 39 ] and periodontitis [ 38 , 39 ] when compared with periodontally healthy controls. However, in agreement with our results, in a previous study difference was not shown at MIF levels in saliva between periodontally healthy, gingivitis and periodontitis patients [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Only periodontitis patients were included in this study to investigate the impact of smoking, which is a major risk factor for periodontal diseases, via tryptophan metabolites. However, gingivitis, the most prevalent form of periodontal disease, can proceed to periodontitis in susceptible individuals if left untreated, emphasizing the significance of early detection and treatment of gingivitis 71 . The transition from gingivitis to the early stages of periodontitis has been associated with an increase in proinflammatory cytokines 72 .…”
Section: Discussionmentioning
confidence: 99%
“…However, gingivitis, the most prevalent form of periodontal disease, can proceed to periodontitis in susceptible individuals if left untreated, emphasizing the significance of early detection and treatment of gingivitis. 71 The transition from gingivitis to the early stages of periodontitis has been associated with an increase in proinflammatory cytokines. 72 The identification of critical salivary biomarkers in gingivitis serves to detect these instances and observe the progression of periodontal disease.…”
Section: Parameters Control (Ns-c) N = 24 Smoker-control (S-c) N = 24...mentioning
confidence: 99%
“…14,22 Moreover, high levels of MIF have been documented in the gingival crevicular fluid, saliva, and serum of individuals with periodontal disease. [23][24][25] The high levels of MIF, in samples from PT patients, suggest that it plays an important role in the physiopathology of periodontal tissues, mainly in free gingiva and junctional epithelium, as well as in keratinocytes, basal cells, and fibroblasts, 26 and probably also plays an important role in osteoclastogenesis. 27 MIF is also expressed in reproductive tissues, and its expression responds to hormonal changes; for example, at low concentrations of estradiol, the expression of MIF is initiated, while at high concentrations of estradiol, the production of MIF is suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…MIF expression has been detected in the epithelial tissue of patients with PT 14,22 . Moreover, high levels of MIF have been documented in the gingival crevicular fluid, saliva, and serum of individuals with periodontal disease 23–25 . The high levels of MIF, in samples from PT patients, suggest that it plays an important role in the physiopathology of periodontal tissues, mainly in free gingiva and junctional epithelium, as well as in keratinocytes, basal cells, and fibroblasts, 26 and probably also plays an important role in osteoclastogenesis 27 …”
Section: Introductionmentioning
confidence: 99%